The Impact of Extracurricular Activities on the Cultural and Linguistic Integration of Non-Native Arabic-Speaking Students - Alsous, Sameer AbdulSalam (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to reveal the impact of extracurricular activities on the cultural and linguistic integration among non-native Arabic-speaking students. Methods: The study employs a one-group quasi-experimental design alongside a descriptive approach. The study sample consists of (17) male and female students. The experimental group was taught by using interactive extracurricular activities tailored to the Jordanian context. The research methods include the pre- and post-achievement tests of linguistic immersion as well as a 36-article questionnaire assessing three dimensions: customs and traditions, moral values, and aesthetic values. The aforementioned methods facilitated extracting adequate validity and reliability benchmarks. Results: The findings reveal statistically significant differences in linguistic immersion, attributed to extracurricular activities for non-native Arabic-speaking students. These differences manifest in students’ enhanced reading, speaking, listening, and writing skills, as well as their mastery of patterns and structures. Moreover, the findings underscore the positive impact of those extracurricular activities on the cultural integration of non-native Arabic-speaking students, particularly in three dimensions: moral values, customs and traditions, and aesthetic values. Conclusion: The study provides a series of recommendations, including attention to linguistic immersion among non-native Arabic-speaking students as well as adopting modern learning strategies to improve the learning and teaching processes for the target group.